1997
DOI: 10.3171/jns.1997.86.3.0438
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of autoregulation using laser Doppler flowmetry in patients with head injury

Abstract: The authors studied 31 comatose head-injured patients to assess the clinical usefulness of laser Doppler flowmetry (LDF) in continuous autoregulation monitoring. The LDF probes were placed on the surface of the cerebral cortex. Data on LDF, intracranial pressure (ICP), and arterial blood pressure (ABP) were recorded and continuously entered into a computer. The data were broken down into multiple segments of 15 minutes' duration (epochs). Epochs showing rapid change in cerebral perfusion pressure (CPP), change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(74 citation statements)
references
References 26 publications
3
71
0
Order By: Relevance
“…When cerebral autoregulation is impaired, cerebral ischemia may ensue if cerebral perfusion pressure (CPP) is low. This is important because adult TBI data suggest that persistently impaired autoregulation is associated with poor outcome (25).…”
Section: Discussionmentioning
confidence: 99%
“…When cerebral autoregulation is impaired, cerebral ischemia may ensue if cerebral perfusion pressure (CPP) is low. This is important because adult TBI data suggest that persistently impaired autoregulation is associated with poor outcome (25).…”
Section: Discussionmentioning
confidence: 99%
“…Adult studies report poor outcomes with permanent but variable outcomes with transient loss of autoregulation [109]. Impaired cerebral autoregulation has been associated with poor outcome after pediatric TBI [104,110], but there is a paucity of information in children.…”
Section: Impaired Cerebral Pressure Autoregulationmentioning
confidence: 99%
“…In similar year, Czosnyka also noted that autoregulation is not only impaired when associated with a high ICP or low arterial blood pressure, but it can also be disturbed by an excessive CPP (Czosnyka et al, 2001). Studies have shown that impairment or failure of autoregulation can contribute to unfavorable outcome (Czosnyka et al, 2001;Lam et al, 1997;Smielewski et al, 1997). This could possibly be explained by a disturbance in the pressure-volume (elastance) curve that is steeper suggesting poor compliance of the brain (figure.…”
Section: Two Major Parameters To Consider During Multimodality Monitomentioning
confidence: 99%